CLINICAL EFFICACY AND SAFETY OF THE COMBINATION OF ROSUVASTATIN AND EZETIMIBE IN THE TREATMENT OF DYSLIPIDEMIA (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article analyzes the clinical efficacy and safety of the combination of rosuvastatin and ezetimibe in the treatment of dyslipidemia. Dyslipidemia is a major risk factor for cardiovascular disease, and while statins are first-line therapy for lowering LDL cholesterol, monotherapy may be insufficient in some patients. Clinical studies demonstrate that the combination therapy provides greater LDL cholesterol reduction compared to monotherapy, with a safety profile similar to statins alone.
Keywords: Rosuvastatin, ezetimibe, dyslipidemia, LDL cholesterol, cardiovascular outcomes, safety profile.